Measurements of dipole moments for the 5s5p3P1-5sns3S1 transitions via Autler-Townes spectroscopy - Tan, Canzhu; Hu, Fachao; Niu, Zhijing; Jiang, Yuhai; Weidemüller, Matthias; Zhu, Bing (Chinese physics letters, 2022)
We report on experimental measurements of the transition dipole moments (TDMs) between the intermediate state 5s5p 3 P 1 and the triplet Rydberg series 5sns 3 S 1 in an ultracold strontium gas. Here n is the principal quantum number ranging from 19 to 40. The transition 5s5p 3 P 1-5sns 3 S 1 is coupled via an ultraviolet (UV) beam, inducing Autler-Townes splitting of both states. Such a splitting of the intermediate state is spectroscopically measured by using absorption imaging on a narrow transition 5s 2 1 S 0-5s5p 3 P 1 in an ultracold gas of strontium atoms. The power and size of the UV beam are carefully determined, with which the TDMs are extracted from the measured Autler-Townes splitting. The experimentally obtained TDMs are compared to the calculations based on a parametric core potential, on a Coulomb potential with quantum defect, and on the open-source library Alkali Ryderg calculator, finding good agreement with the former two models and significant deviation with the latter.
Im Titel ist die 3 hochgestellt, die1 tiefgestellt
Gesehen am 27.10.2022